2015
DOI: 10.1016/j.gca.2015.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Competitive sorption of CO2 and H2O in 2:1 layer phyllosilicates

Abstract: Expandable clays such as montmorillonite have interlayer exchange sites whose hydration state can be systematically varied from near anhydrous to almost bulk-like water conditions. This phenomenon has new significance with the simultaneous implementation of geological sequestration and secondary utilization of CO 2 to both mitigate climate warming and enhance extraction of methane from hydrated clay-rich formations. In this study, the partitioning of CO 2 a n d H 2 O between Na-, Ca-, and Mg-exchanged montmori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

43
202
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(247 citation statements)
references
References 56 publications
43
202
2
Order By: Relevance
“…In a very recent study Schaef et al (2015) demonstrated, using XRD, IR and quartz crystal microbalance (QCM) on variably hydrated Ca-SWy2, that the swelling depends on the relative amounts of H 2 O and CO 2 in the interlayer. The interlayer space of dry smectite increases sharply upon introduction of some water, and decreases again upon further hydration of the clay.…”
Section: Co 2 Sorption On Clay Mineralsmentioning
confidence: 99%
“…In a very recent study Schaef et al (2015) demonstrated, using XRD, IR and quartz crystal microbalance (QCM) on variably hydrated Ca-SWy2, that the swelling depends on the relative amounts of H 2 O and CO 2 in the interlayer. The interlayer space of dry smectite increases sharply upon introduction of some water, and decreases again upon further hydration of the clay.…”
Section: Co 2 Sorption On Clay Mineralsmentioning
confidence: 99%
“…Adsorption/absorption is reported when the mechanism is not clear. However, recent work suggests that absorption into the interlayer is the dominant process particularly at lower pressures below the critical point (Schaef et al, 2015). Spectra were collected until the CO 2 adsorption/absorption bands no longer changed with time.…”
Section: Infrared Spectroscopymentioning
confidence: 99%
“…[30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][52][53][54][55][56] With respect to confinement of hydrophobic species, the 2-dimensional interlayer galleries of expandable clays are known to accommodate CO 2 . 6,[18][19][20][21]23,26,38,[57][58][59][60][61][62][63][64] Owing to their natural abundance, environmental friendliness, large internal surface areas, and tunable affinity and specificity for adsorption of small and complex molecules, 37-45,53-56 the expandable clay minerals continue to serve as ideal models for understanding the behavior of hydrophilic and hydrophobic species in …”
mentioning
confidence: 99%
“…[18][19][20][21][22][23][24][25][26][27][28][29]58 For instance, Schaef et. al., 62 estimated the amount of CO 2 in the interlayer of dry sodium montmorillonite (Na-MMT) using quartz crystal microbalance (QCM) measurements while Loring et. al., 20 examined the hydration-dependent variation of the IR-derived integrated absorbance of the asymmetric CO stretching band of the interlayer CO 2 molecules to quantify the amount of CO 2 in the interlayer of Na-MMT at 50 0 C and 90 bar.…”
mentioning
confidence: 99%
See 1 more Smart Citation